The TeRiFiQ project: Combining technologies to achieve significant binary reductions in sodium, fat and sugar content in everyday foods whilst optimising their nutritional quality. Issue 4 (10th November 2017) - Salles, C.; Kerjean, J. R.; Veiseth‐Kent, E.; Stieger, M.; Wilde, P.; Cotillon, C.; ,
Abstract: Most developed countries are confronted with rising rates of diseases related to unhealthy eating habits, particularly the excessive consumption of salt, saturated fat and free sugars. However, fat, sugars and salt in food influence not only its nutritional qualities but also its sensory properties, safety ( e.g . shelf life) and affordability. The main challenge is to formulate healthier foods that are acceptable to consumers. In this context, the overall objective of TeRiFiQ was to achieve significant binary reductions in the salt‐fat and sugar‐fat contents of frequently consumed food products around Europe, while, at the same time, ensuring the products' nutritional and sensorial qualities, safety and affordability for both industry and consumers was not compromised. TeRiFiQ addressed four major food categories: cheeses, processed meat, bakery and sauce products. Different strategies adapted to each food category were used to reduce the target ingredients. Significant reductions in the salt‐fat and fat‐sugar contents of a number of cheese, processed meat, bakery and sauce products were achieved, and these changes were found to be acceptable to consumers. The most promising reformulated food products were developed at the industrial scale.